2019
DOI: 10.3847/1538-3881/aafa72
|View full text |Cite
|
Sign up to set email alerts
|

A Pluto–Charon Sonata: The Dynamical Architecture of the Circumbinary Satellite System

Abstract: Using a large suite of n-body simulations, we explore the discovery space for new satellites in the Pluto-Charon system. For the adopted masses and orbits of the known satellites, there are few stable prograde or polar orbits with semimajor axes a 1.1 a H , where a H is the semimajor axis of the outermost moon Hydra. Small moons with radii r 2 km and a 1.1 a H are ejected on time scales ranging from several yr to more than 10 Myr. Orbits with a 1.1 a H are stable on time scales exceeding 100 Myr. Near-IR and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 201 publications
(236 reference statements)
0
11
0
Order By: Relevance
“…If Charon's eccentricity reaches the values expected in current tidal models (Cheng et al, 2014b), some or all of the satellites except Hydra become dynamically unstable on their present-day orbits (Smullen and Kratter, 2017). As mentioned above, this model also predicts the growth and survival of small satellites exterior to Hydra (e.g., Kenyon and Bromley, 2019); such satellites have not been seen to date (section 2.3). Walsh and Levison (2015) considered the evolution of debris from one or more disrupted outer satellites that formed as a result of a Charon-forming impact.…”
Section: Hybrid Models: Charon Impact Debris Interacts With Heliocentric Debrismentioning
confidence: 81%
See 3 more Smart Citations
“…If Charon's eccentricity reaches the values expected in current tidal models (Cheng et al, 2014b), some or all of the satellites except Hydra become dynamically unstable on their present-day orbits (Smullen and Kratter, 2017). As mentioned above, this model also predicts the growth and survival of small satellites exterior to Hydra (e.g., Kenyon and Bromley, 2019); such satellites have not been seen to date (section 2.3). Walsh and Levison (2015) considered the evolution of debris from one or more disrupted outer satellites that formed as a result of a Charon-forming impact.…”
Section: Hybrid Models: Charon Impact Debris Interacts With Heliocentric Debrismentioning
confidence: 81%
“…High small moon albedos were first predicted from the dynamical models of Youdin et al (2012), who found that lower albedos, which required larger moon masses for consistency with HST data, would lead to dynamical instability. Subsequent orbital analyses have confi rmed that stability requires high albedos and low moon masses, and in the case of Hydra, have pushed its estimated mass to even lower values (Brozović et al, 2015;Kenyon and Bromley, 2019;Jacobson et al, 2019).…”
Section: Properties Of the Small Moonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Albedos are ∼55% for Kerberos and Nix, 65% for Styx, and 85% for Hydra (Weaver et al 2016). Although smaller satellites could exist slightly inside the orbit of Styx and outside the orbit of Hydra (Kenyon & Bromley 2019b), there are no 2 km satellites and a negligible amount of dust between the orbits of Styx and Hydra (Weaver et al 2016;Lauer et al 2018).…”
Section: Introductionmentioning
confidence: 99%